2021
DOI: 10.1186/s12902-021-00837-z
|View full text |Cite
|
Sign up to set email alerts
|

The susceptibility of SERPINE1 rs1799889 SNP in diabetic vascular complications: a meta-analysis of fifty-one case-control studies

Abstract: Background The serine protease inhibitor-1 (SERPINE1) rs1799889 single nucleotide polymorphism (SNP) has been constantly associated with diabetes mellitus (DM) and its vascular complications. The aim of this meta-analysis was to evaluate this association with combined evidences. Methods The systematic search was performed for studies published up to March 2021 which assess the associations between SERPINE1 rs1799889 SNP and the risks of DM, diabeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
2
0
0
1
Order By: Relevance
“…Taking into account the discrepancy in findings derived from different study, it could be suggested that genetic variability in SERPINE1 is influenced by the ethnicity and/or type of diabetes, as many studies conducted in Asians with T2DM detected significant association between genetic variants of SERPINE1 and DN, whereas studies performed in Caucasians with T1DM did not detect any significant association between SERPINE1 and DN. Our suggestion is in agreement with the conclusion of a recent meta-analysis of SERPINE1 rs1799889 variant, in which Chen et al (2021) concluded that 4G polymorphism could constitute a genetic synergistic factor in overall DM and DN populations, positively for individuals with Asian descent [ 49 ]. It is noteworthy to be mentioned that the association of rs1799889 variant was not revealed significant in diabetic retinopathy and cardiovascular risks [ 49 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Taking into account the discrepancy in findings derived from different study, it could be suggested that genetic variability in SERPINE1 is influenced by the ethnicity and/or type of diabetes, as many studies conducted in Asians with T2DM detected significant association between genetic variants of SERPINE1 and DN, whereas studies performed in Caucasians with T1DM did not detect any significant association between SERPINE1 and DN. Our suggestion is in agreement with the conclusion of a recent meta-analysis of SERPINE1 rs1799889 variant, in which Chen et al (2021) concluded that 4G polymorphism could constitute a genetic synergistic factor in overall DM and DN populations, positively for individuals with Asian descent [ 49 ]. It is noteworthy to be mentioned that the association of rs1799889 variant was not revealed significant in diabetic retinopathy and cardiovascular risks [ 49 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our suggestion is in agreement with the conclusion of a recent meta-analysis of SERPINE1 rs1799889 variant, in which Chen et al (2021) concluded that 4G polymorphism could constitute a genetic synergistic factor in overall DM and DN populations, positively for individuals with Asian descent [ 49 ]. It is noteworthy to be mentioned that the association of rs1799889 variant was not revealed significant in diabetic retinopathy and cardiovascular risks [ 49 ].…”
Section: Discussionsupporting
confidence: 93%
“…* -the significance of the differences was calculated relative to the corresponding indicators of 1 st group. показателям европейской популяции [12]. Продуктом гена SERPINE1 является белок РАI-1 (plasminogen activator inhibitor-1), основная функция которого ингибировать активатор плазминогена как клеточного, так и урокиназного типа [13].…”
Section: таблица 1 генотипы и аллели полиморфных локусов генов в груп...unclassified